2021
DOI: 10.2147/copd.s283005
|View full text |Cite
|
Sign up to set email alerts
|

Poor Work Efficiency is Associated with Poor Exercise Capacity and Health-Related Quality of Life in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is a progressive disease with deteriorating cardiopulmonary function that decreases the health-related quality of life (HRQL) and exercise capacity. Patients with COPD often have cardiovascular and muscular problems that hinder oxygen uptake by peripheral tissues, resulting in poor oxygen consumption efficiency. It is important to develop new physiological parameters to evaluate oxygen consumption efficiency during activities and to evaluate its associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…By consulting library books and querying databases such as CNKI and Wanfang, and referring to a large number of journals and master's and doctoral dissertations on functional training and physical fitness, sort out and analyze the frontier knowledge and theories of predecessors in this field, and apply them to the author's writing, providing important guidance for the author's writing. 8…”
Section: Methods Documentation Methodsmentioning
confidence: 99%
“…By consulting library books and querying databases such as CNKI and Wanfang, and referring to a large number of journals and master's and doctoral dissertations on functional training and physical fitness, sort out and analyze the frontier knowledge and theories of predecessors in this field, and apply them to the author's writing, providing important guidance for the author's writing. 8…”
Section: Methods Documentation Methodsmentioning
confidence: 99%
“…Patients were encouraged to do their best to achieve maximal possible performance. The anaerobic threshold (AT) was determined using a VCO 2 versus VO 2 plot 9 …”
Section: Methodsmentioning
confidence: 99%
“…The dyspnea and leg fatigue scores at peak exercise during the CPET were evaluated using a Borg scale with 10‐point scores. Higher scores indicated more dyspnea or leg fatigue 9 …”
Section: Methodsmentioning
confidence: 99%
“…Maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) were measured five times with a pressure gauge (Respiratory Pressure Meter; Micro Medical Corp, England), and the highest value was recorded. 4 , 10 For the measurement of MIP, the patients exhaled to the residual volume and then perform a rapid maximal inspiration. For the measurement of MEP, the patients inhaled to the total lung capacity and then exhaled with maximal effort.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that COPD patients with a poor WE also had early anaerobic metabolism, lower exercise capacity, more exertional dyspnea, and poorer HRQL. 4 However, whether WE affects the effect of PR in COPD patients with a poor WE remain unknown.…”
Section: Introductionmentioning
confidence: 99%